"We Are Book Eight": Dialoging the collective imagination through literary fan activism. (December 2018) - Carriere, Kevin R
This paper will explore how individuals employ imagination through collective action. First, I will outline a definition of imagination, focusing on how the dialogic nature of imagination provides an overarching framework for individuals focused on producing change. Next, I will discuss symbolic resources as a way to link one's imagination with another's. Qualitative interviews from The Harry Potter Alliance will be examined as a case where collective action is taken through shared resources. It will highlight how placing real-world issues in dialogue with imaginary constructs can assist in sharing imaginations toward worlds of what-if . Discussions around the relational aspect of collective imagination will end the paper.